A new snake of the genus Helicops Wagler, 1830 (Dipsadidae, Xenodontinae) from Brazil - Kawashita-Ribeiro, Ricardo Alexandre; Ávila, Robson Waldemar; Morais, Drausio Honorio [UNESP] (Herpetologists League, 2013)
We describe a new species of Helicops from the southern Amazon Basin in the state of Mato Grosso, Brazil. It differs from all congeners by having dorsal scales in 21/21/19 rows in males and 23/21/19 rows in females, subcaudal keels, a banded dorsal color pattern, and 14-19 ventral blotches. Besides presenting information on the lepidosis and morphometric variation, we also describe the hemipenis and discuss the known distribution of the new species. © 2013 by The Herpetologists' League, Inc.
Keywords: Amazon Basin; Hydropsini; Neotropical; Squamata; biological characteristics; color; geographical distribution; morphology; morphometry; Neotropical Region; new species; snake; Brazil; Mato Grosso